Investigation of antimagnetic rotation in 101Pd. (6th June 2017) - Singh, V; Sihotra, S; Roy, S; Kaur, M; Saha, S; Sethi, J; Palit, R; Singh, N; Malik, S S; Jain, H C; Mehta, D
Abstract: Excited states in the 101 Pd isotope were investigated following the 75 As( 31 P, 2 p 3 n ) 101 Pd reaction at E lab = 125 MeV. In-beam γ -ray measurements were performed using the Indian National Gamma Array (INGA) spectrometer consisting of 21 Compton-suppressed clover detectors. Level lifetimes have been measured for the negative-parity ν h 11 / 2 band in 101 Pd using the Doppler-shift attenuation method up to the 43/2 − state and are found to differ substantially from the recently reported values. The deduced quadrupole transition rates exhibit a monotonically decreasing behaviour with increasing angular momentum in the spin range 31 / 2 ℏ ≤ I ≤ 43 / 2 ℏ along with large I ( 2 ) / B ( E 2 ) values (>300 ℏ 2 MeV − 1 ( eb ) − 2 ). Using the semiclassical particle-rotor model, the observed band characteristics are interpreted as antimagnetic rotation based on the π ( g 9 / 2 ) − 2  ⨂  ν [ h 11 / 2 ( g 7 / 2 ) 2 ] configuration. The configuration assignment is also favoured by the cranking shell model calculations.